Improving parish youth engagement - Mallari, Michael D. (Animo Repository, 2018)
In this action research, I focused on addressing the issue in our parish which we collaboratively identified as the declining level of engagement among our youth parishioners. Work engagement as defined by Macey and Schneider (2008) is a desirable condition that has organizational purpose. It consists of several aspects such as positive traits, state of involvement and empowerment, and proactive behavior. Manifestations of declining parish youth engagement include declining church attendance, declining interest to participate on church works, and perceived lack of parental support. This action research was developed with the objectives of: (1) engaging youth in meaningful church activities; (2) providing avenues for personal devotion, prayer, and reflections; and (3) reaching out to the non-member parents of our youth parishioners. By achieving these objectives, our goal was to deepen the spiritual life of our youth. As an insider action researcher, I applied triangulation of data in data generation by using different methods of data collection such as pure inquiries, inquiries through formal meetings, focus group discussions, and one-on-one discussions. In addressing the issue, I was guided by the Zinger Model of Employee Engagement and Kurt Lewins Change Management Model. We identified the key areas of engagement which we needed to work on and used Lewins Change Management Model to effect change in the organization. We implemented technostructural interventions to address the issue on declining youth engagement. The first cycle of intervention related to the various aspects of High-Involvement Organizations (HIOs) catered for the Youth Ministry (Cummings, et. al., 2008). Our second cycle meanwhile focused on reducing physical barriers to engagement through the implementation of a Parish Website. These activities were successful in achieving our objectives for this project. In doing this project, I realized that for a parish community to grow, it must start with a commitment to being sensitive to the needs of others no matter how trivial it may seem. The experience taught me the value of critical and creative thinking, reflective lifelong learning, and effective communication. Ironically, I learned to become more concerned about the welfare and well-being of our youth and not just on how they participated in our activities. The most rewarding part of this project was being a change agent in my own organization. For the next cycle, I recommend focusing on the other areas of the Zinger Model such as maximizing youth performance, plotting out ministry progression, fostering recognition, and enhancing well-being. These are consistent with the Career Systems area of HIOs to help provide youth members with different opportunities for advancement and growth. These areas are also vital in coming up with a holistic approach to parish youth engagement.